Barter, Liquidity and Market Segmentation - Canice Prendergast; Lars Stole (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper explores the private and social benefits from barter exchange in a monetized economy. We first prove a no-trade theorem regarding the ability of firms with double-coincidences-of-wants to negotiate improvements in trade among themselves relative to the market outcomes. We then demonstrate that in the presence of liquidity shocks, introducing a non-monetary exchange avoids this limitation and enhances trade by (1) generating liquidity and (2) by segmenting the market place into low-demand and high-demand customers in a manner which is impossible with pure monetary exchange. We provide comparative statics illustrating the importance of each effect and relevant extensions.
Keywords: 330; barter; exchange